Flibanserin for hypoactive sexual desire disorder: place in therapy. (January 2017) - Gelman, Faina; Atrio, Jessica
The pathophysiology, diagnosis and treatment of female sexual interest in pre- and post-menopausal women present a complex arena for patients and physicians to navigate. Flibanserin was the first pharmacologic treatment, approved by the United States Food and Drug Administration in August 2015, for hypoactive sexual desire disorder (HSDD) in premenopausal women. Side effects, contraindications and lack of approval in postmenopausal women are all limitations, as are issues surrounding patient and physician knowledge and access. Testosterone, buspirone, sildenafil, bupropion, bremelanotide, as well as herbal medications (Herbal vX or Tribulus terrestris ) have demonstrated some clinical benefit in women with sexual dysfunction disorders however, trials have significant design, dosing or generalizability limitations. Nonpharmaceutical cognitive behavioral therapy, mindfulness meditation, pelvic floor therapy, and clitoral stimulators are also interventions women may pursue. This manuscript will explore the clinical data regarding these therapeutic modalities so as to bring attention to this issue of female HSDD, to offer an overview of current research, and to incite providers to initiate discussion among themselves and their patients.